KEBIJAKAN PEMEKARAN KECAMATAN DAN PELAYANAN MASYARAKAT - Amir Amir; Sujianto Sujianto; Febri Yuliani (Universitas Riau, 2018)
Policies of District Expansion and Community Service. This study aims to determinethe efforts of the policy of accelerating the expansion of the districts and to determine what factorsare related to the policy of the expansion of the districts. The type of research is a qualitativeapproach. The research informants were 12 people taken by the Chairman and Members of DPRD,Chairman and Members of BPD, Bureau of Government, Sekcam, Village Head and CommunityLeader. Data collection techniques that the author did with observation, Documentation, andinterviews. Analysis of data that the authors used in this study is an interactive analysis model. Theresults of the research show that the district of Bantan has not been bloomed because there hasbeen no proposal about the pemekaran from the village of Bantan kecmatan. Bantan sub-districtinhibiting factors are not established ie no good communication exists between the village andsub-district, as well as communication between the regional head and the regional parliament onthe expansion of the districts. In terms of resources, there is no expert to conduct an assessment ofsub-district pemekaran. As for the disposition they agreed but none became the implementor of thepolicy of the expansion of the districts. Furthermore, about the bureaucracy in doubt of the newlaw, namely Law No. 23 of 2014 on local government has not replaced government regulation No.19 of 2008 on the district.